“The city of their fathers”: Urban Space, Memory, and Language in Stuart Dybek’s Short Fiction - Kimak, Izabella (Text Matters: A Journal of Literature, Theory and Culture, 2025)
Stuart Dybek is a writer invariably associated with his neighborhood of Pilsen/Little Village on Chicago’s Lower West Side. Having grown up there as a descendant of immigrants from Poland, Dybek frequently “revisits” his old neighborhood in his writing. His texts showcase the changes of the urban space, narrated through references to the material, social, cultural, and linguistic environment. In this essay, I will analyze two of Dybek’s texts—the sequence “Hot Ice” from his second collection of stories The Coast of Chicago and the story “Qué Quieres” from I Sailed with Magellan—to probe the palimpsestic construction of urban space, whereby the past, present, and future of urban orders are narrated simultaneously. Both texts illustrate ethnic succession in the neighborhood—from Slavs to Hispanics—which finds its reflection in the linguistic layer of the stories and construes translation as an inevitable element of urban experience.